The Influence of Price, Online Customer Reviews, and Product Quality on Purchasing Decisions at the Pretties Online Store "Sukoharjo" - Sariwibowo, Rindu Warih; Darsono, Darsono; Husin, Syahri Al (ProBisnis : Jurnal Manajemen, 2025)
This study aims to determine the effect of Price, Online Customer Review, and Product Quality on Purchasing Decisions at the Pretties "Sukoharjo" Online Store. The use of the purposive sampling method so that 100 respondents were obtained. Respondent data were obtained by distributing questionnaires that had been prepared to respondents through online media. From a population of 100 people, using the probability sampling technique. The number of samples obtained was 100 people. The analysis used was multiple linear regression using SPSS Version 25. Based on the results of the analysis, it was found that the Influence of Price, Online Customer Review and Product Quality had a positive and significant effect on purchasing decisions at the Pretties "Sukoharjo" Online Store. The findings indicate that Price partially influences Purchasing Decisions by 17.4%, Online Customer Reviews by 20.6%, and Product Quality by 60.6%. Simultaneously, these three variables significantly influence Purchasing Decisions, with a significance value of 0.000 < 0.05. The coefficient of determination reveals that the independent variables in this study collectively explain 83.3% of the variance in the dependent variable, while the remaining 16.7% is influenced by other factors not examined in this study.